Corporate Social Responsibility of Coal Comodity Industry in Indonesia - Solihudin, Ahmad Rizal; Danica; Kurniawan, Mahrus Lutfi Adi (UMSurabaya Publishing, 2024)
The concept of Corporate Social Responsibility (CSR) continues to develop following the rapid development of business models and awareness of various groups regarding CSR issues. The implementation of CSR has been carried out by companies at various levels, from multinational, national to local companies, especially in Indonesia. This research aims to analyze the CSR performance of coal companies in Indonesia by measuring leverage, profitability and company size. The data collection method uses content analysis techniques in annual reports of coal companies listed on the IDX. The testing method uses panel data regression. Hypothesis test results show that company size and probability influence corporate social responsibility (CSR). Meanwhile, leverage shows a positive and significant influence on corporate social responsibility (CSR).